(untitled) (Med Phoenix, 2018)
Ascariasis is the most prevalent helminthic infection to infest human beings caused by Ascaris lumbricoides. Rarely the worm migrates through ampulla of Vater and may enter common bile duct. This is a case report of live Ascaris lumbricodes in gallbladder, on USG. Med Phoenix. Vol. 3, Issue. 1, 2018, Page: 95-97